BOOK REVIEW: Elizabeth M. Schneider, Battered Women and Feminist Lawmaking (New Haven: Yale University Press, 2000) - Groisser, Suzanne J. (Columbia Journal of Gender and Law, 2001)
Domestic violence is a problem of epidemic proportions plaguing our society. Nearly 1.9 million women are battered each year in the United States’ and approximately sixty percent of all women murdered are killed by a present or former intimate partner. While there have been important advances in legal remedies for battered women over the past twenty years, including federal legislation such as the Violence Against Women Act and state laws specifically addressing domestic violence, there remain many obstacles-legal and social-which battered women, their advocates and attorneys, and legal scholars must confront. Given the prevalence of these problems, the issue of domestic violence should no longer be marginalized nor omitted from law school curricula. In Battered Women and Feminist Lawmaking, Brooklyn Law School Professor Elizabeth Schneider provides an outstanding critical overview of the history of the battered women’s movement and the complex legal and social issues facing battered women. This book is unique in the way it challenges the legal approaches historically used to address the issue of battering and provides both a theoretical and practical roadmap for legal and social reform. Schneider adopts a feminist theoretical approach, which links theory with practice, to analyze the legal and social responses to domestic violence over the last two decades. At the core of this book is the call to recognize that domestic violence is not an isolated problem, but, rather, is embedded in gender inequality that permeates our society.